Protracted circum-continent subduction: A mechanism for craton destruction and a rationale for craton longevity - Xi Xu; Andrew V. Zuza; Lijun Liu; Weilin Zhu; Yanyun Sun; Baodi Wang; Xingtao Kuang; Song Han; Xuanjie Zhang; Wan Zhang; Xiaowei Fu; D. Graham Pearson; et al. (Proceedings of the National Academy of Sciences, 2025)
The evolution of continents is shaped by the growth and destruction of long-lived cratons, which serve as their stable cores. Processes for craton destruction are controversial because most invoked mechanisms occur frequently throughout Earth history, making the preservation of cratons for billions of years problematic. Here, we address this issue by presenting a crustal-scale analytical signal-amplitude model obtained from high-resolution airborne and shipborne magnetic data across cratons within East Asia. Magmatic, magnetic, and basin-history constraints show that the eastern North China craton experienced focused weakening, thickening, and catastrophic destruction of its mantle lithosphere due to a unique combination of circum-craton subduction and subsequent collision since the Paleozoic. By contrast, the adjacent South China craton was not impacted in this way, and thus, its mantle root was spared from destruction. The long-term survival of cratons may stem from the infrequent occurrence of sustained circum-cratonic subduction or collisional processes capable of destabilizing their lithospheric roots.